Pendidikan Karakter Berbasis Al-Quran - Dewi Purnamasari (Institut Agama Islam Negeri (IAIN) Curup, 2017)
This article discusses the problem of character education. Character education into the spotlight of attention lately because of the decline, which resulted in the decline of morals. In the Qur'an, the characters use the term